Water Masses Variability in Inner Kongsfjorden (Svalbard) During 2010–2020 - De Rovere, Francesco; Langone, Leonardo; Schroeder, Katrin; Miserocchi, Stefano; Giglio, Federico; Aliani, Stefano; Chiggiato, Jacopo (Frontiers in Marine Science, 2022)
Kongsfjorden is an Arctic fjord located in the Svalbard archipelago. Its hydrography is influenced by the warm and saline Atlantic Waters (AW) in the West Spitsbergen Current and the cold and fresh Polar Waters circulating on the shelf. We assess the so-called atlantification of Kongsfjorden in the 2010-2020 decade by inspecting modifications in water properties and water masses variability through moored data and summer CTD surveys. Atlantification in this fjord has emerged as an increasing temperature and salinity, resulting from enhanced advection of Atlantic waters from the West Spitsbergen Current. The water column in inner Kongsfjorden warmed by 0.13 °C/yr at 35 m and 0.06 °C/yr at 85 m depth from 2010 to 2020, while salinity increased by 0.3 PSU. Depth-averaged temperatures have increased by 0.26 °C/yr in the warmest months of the year, whereas they appear relatively stable in the coldest months. Both temperature and salinity present a linear regression change point in January 2017, with latter years featuring decreasing values. Highly diluted AW are found at the beginning of the decade, which give way to more and more pure AW in latter years, culminating in extensive intrusions in 2016 and 2017 determining the warmest and saltiest conditions over the decade in inner Kongsfjorden. Observations in the 2010-2020 decade confirm that Kongsfjorden has transitioned to an Atlantic-type fjord, featuring depleted sea ice conditions and rather regular shallow intrusions of AW waters in summer and frequently also in winter. Although single intrusions of AW are associated with dynamical events on the shelf, we found that the long-term temperature evolution in the inner Kongsfjord is consistent with the meridional temperature transport of the West Spitsbergen Current. The Atlantic water current flowing northward from lower latitudes along the western Svalbard archipelago thus has profoundly driven local conditions in the inner fjord in this decade.